P14 Pirfenidone is efficacious in patients with idiopathic pulmonary fibrosis (IPF) with more preserved lung function. (12th November 2015) - Noble, PW; Bradford, WZ; Costabel, U; Glaspole, I; Glassberg, MK; Gorina, E; Kardatzke, D; Lancaster, L; Lederer, DJ; Nathan, SD; Pereira, C; Spirig, D; et al.
Abstract : Introduction and objectives: IPF is a progressive, irreversible and fatal disease. Early treatment initiation when lung function is relatively preserved may have beneficial outcomes; however, published data to support this hypothesis are lacking. We investigated the efficacy of pirfenidone at 12 months in patients stratified by lung function using forced vital capacity (FVC) or GAP stage. Methods: Efficacy outcomes (FVC, 6-minute walk distance [6MWD] and dyspnea [UCSD SOBQ]) were analysed at 12 months in patients randomised to pirfenidone 2403 mg/d or placebo in the pooled CAPACITY/ASCEND population (N = 1247), stratified by baseline FVC (≥80%, <80%) and GAP stage (GAP I, GAP II-III). Treatment-by-subgroup interaction was tested based on a rank ANCOVA model. The factors in the model included study, region, treatment, subgroup and treatment-by-subgroup interaction term. Results: Demographic characteristics were similar across all four groups. In the placebo arm, disease progression as measured by FVC occurred with comparable frequency in patients with FVC ≥80% and FVC <80%, as well as in patients with GAP I and GAP II-III stage. A higher proportion of placebo patients with FVC <80% and GAP II-III stage had a ≥50-m decline in 6MWD or death or a ≥20-point change in the UCSD SOBQ total score. Pirfenidone treatment reduced the proportion of patients experiencing a ≥10% FVC decline or death and increased the proportion of patients with no FVC decline in all subgroups. Pirfenidone also reduced the proportion of patients with ≥50-m decline in the 6MWD or death and increased the proportion of patients with no 6MWD decline in all subgroups. The magnitude of treatment effect in patients with less vs more preserved lung function was comparable, with no significant treatment-by subgroup interaction (Figure 1 ). Conclusions: In the placebo population, clinically significant disease progression occurs in subgroups with more and less preserved lung function at baseline, underlying the need for early intervention. The magnitude of pirfenidone treatment effect on functional measures was comparable in these subgroups of patients (FVC <80% vs FVC ≥80% or GAP I vs GAP II-III stage), supporting the initiation of treatment soon after diagnosis, when pulmonary function is relatively preserved.